Ac2-26 peptide and serine protease of Bothrops atrox similarly induces angiogenesis without triggering local and systemic inflammation in a murine model of dorsal skinfold chamber. (October 2017) - Molás, Rafaela Batista; de Paula-Silva, Marina; Masood, Rehana; Ullah, Anwar; Gimenes, Alexandre Dantas; Oliani, Sonia Maria
Highlights: The dorsal skin chamber is a versatile tool to observe the angiogenic process. Ac2-26 peptide from annexin A1 protein and serine protease of Bothrops atrox promote new blood vessels formation. These mediators do not induce inflammatory cells recruitment and changes in cytokines levels.